SARS-CoV-2 and Environmental Changes: The Perfect Storm - Mario Caldarelli; Pierluigi Rio; Vincenzo Giambra; Ivana Palucci; Antonio Gasbarrini; Giovanni Gambassi; Rossella Cianci (Current Issues in Molecular Biology)
The COVID-19 pandemic has had a significant impact on the global economy. It also provided insights into how the looming global climate crisis might be addressed, as there are several similarities between the challenges proposed by COVID-19 and those expected from the coming climate emergency. COVID-19 is an immediate health threat, but climate change represents a more gradual and insidious risk that will lead to long-term consequences for human health. Research shows that climate change, air pollution and the pandemics have a negative impact on health. Recent studies show that COVID-19 mortality increases with climate extremes. The goal of our review is to analyze the clinical findings of COVID-19 and how they are affected by the climate change, while also providing insight into the emergence of new variants and their ability to evade the immune system. We selected and synthesized data from primary studies, reviews, meta-analyses, and systematic reviews. Selection was based on rigorous methodological and relevance criteria. Indeed, a new variant of SARS-CoV-2, named JN.1, has emerged as the dominant, first in the United States and then worldwide; the variant has specific mutations in its spike proteins that increase its transmissibility. According to the World Health Organization (WHO), JN.1 is currently the most reported variant of interest (VOI), having been identified in 132 countries. We highlight the link between climate change and pandemics, emphasizing the need for global action, targeted medical approaches and scientific innovation.